Synthesis of new, highly luminescent bis(2,2’-bithiophen-5-yl) substituted 1,3,4-oxadiazole, 1,3,4-thiadiazole and 1,2,4-triazole - Kostyuchenko, Anastasia S.; L.Yurpalov, Vyacheslav; Kurowska, Aleksandra; Domagala, Wojciech; Pron, Adam; Fisyuk, Alexander S. (Beilstein Journal of Organic Chemistry, 2014)
A new synthetic approach towards the preparation of functionalised, soluble, donor–acceptor (DA) alkylbithiophene derivatives of oxadiazole, thiadiazole and triazole is reported. Taking advantage of the Fiesselmann reaction, reactive bithiophene synthons having alkyl or alkoxy substituents at designated positions are prepared. Following a synthetic strategy, featuring the bottom-up approach, sequential structural elements are built, starting from a simple thiophene compound, until the target molecule is obtained, all in good yield. Supplementing the well established methods of oxadiazole and thiadiazole synthesis, efficient ring closure reaction affording a 4H-1,2,4-triazole unit is presented. All target ambipolar compounds display strong photoluminescence with measured quantum yields up to 0.59. Modification of the demonstrated synthetic routes may be exploited for the preparation of longer, specifically functionalised oligothiophenes, coupled to other heteroaromatic cores.
Keywords: bithiophene; donor–acceptor; luminescence; 1,3,4-oxadiazole; 1,3,4-thiadiazole; 4H-1,2,4-triazole

(untitled) - Mishra, A.; Ma, C.-Q.; Bäeuerle, P. (Chem. Rev., 2009)

(untitled) - Pron, A.; Gawrys, P.; Zagorska, M.; Djurado, D.; Demadrille, R. (Chem. Soc. Rev., 2010)

(untitled) - Hains, A. W.; Liang, Z.; Woodhouse, M. A.; Gregg, B. A. (Chem. Rev., 2010)

(untitled) - Cheng, Y.-J.; Yang, S.-H.; Hsu, C.-S. (Chem. Rev., 2009)

(untitled) - Bujak, P.; Kulszewicz-Bajer, I.; Zagorska, M.; Maurel, V.; Wielgus, I.; Pron, A. (Chem. Soc. Rev., 2013)

(untitled) - Marszalek, T.; Kucinska, M.; Tszydel, I.; Gravalidis, C.; Kalfagiannis, N.; Logothetidis, S.; Yassar, A.; Miozzo, L.; Nosal, A.; Gazicki-Lipman, M.; Jung, J.; Ulanski, J. (Opt. Mater., 2012)

(untitled) - Lee, M. J.; Gupta, D.; Zhao, N.; Heeney, M.; McCulloch, I.; Sirringhaus, H. (Adv. Funct. Mater., 2011)

(untitled) - Lee, M. J.; Chen, Z.; di Pietro, R.; Heeney, M.; Sirringhaus, H. (Chem. Mater., 2013)

(untitled) - Hartmann, L.; Tremel, K.; Uttiya, S.; Crossland, E.; Ludwigs, S.; Kayunkid, N.; Vergnat, C.; Brinkmann, M. (Adv. Funct. Mater., 2011)

(untitled) - Kurach, E.; Kotwica, K.; Zapala, J.; Knor, M.; Nowakowski, R.; Djurado, D.; Toman, P.; Pfleger, J.; Zagorska, M.; Pron, A. (J. Phys. Chem. C, 2013)

(untitled) - Kotwica, K.; Kurach, E.; Louarn, G.; Kostyuchenko, A. S.; Fisyuk, A. S.; Zagorska, M.; Pron, A. (Electrochim. Acta, 2013)

(untitled) - McCairn, M. C.; Kreouzis, T.; Turner, M. L. (J. Mater. Chem., 2010)

(untitled) - Zapala, J.; Knor, M.; Jaroch, T.; Maranda-Niedbala, A.; Kurach, E.; Kotwica, K.; Nowakowski, R.; Djurado, D.; Pecaut, J.; Zagorska, M.; Pron, A. (Langmuir, 2013)

(untitled) - Mitschke, U.; Mena Osteritz, E.; Debaerdemaeker, T.; Sokolowski, M.; Bäuerle, P. (Chem.–Eur. J., 1998)

(untitled) - Mitschke, U.; Debaerdemaeker, T.; Bäuerle, P. (Eur. J. Org. Chem., 2000)

(untitled) - Fisyuk, A. S.; Demadrille, R.; Querner, C.; Zagorska, M.; Bleuse, J. L.; Pron, A. (New J. Chem., 2005)

(untitled) - Lee, T.; Landis, C. A.; Dhar, B. M.; Jung, B. J.; Sun, J.; Sarjeant, A.; Lee, H.-J.; Katz, H. E. (J. Am. Chem. Soc., 2009)

(untitled) - Clavier, G.; Audebert, P. (Chem. Rev., 2010)

(untitled) - Gong, Y.-H.; Miomandre, F.; Méallet-Renault, R.; Badré, S.; Galmiche, L.; Tang, J.; Audebert, P.; Clavier, G. (Eur. J. Org. Chem., 2009)

(untitled) - Audebert, P.; Sadki, S.; Miomandre, F.; Clavier, G. (Electrochem. Commun., 2004)

(untitled) - Grykien, R.; Luszczynska, B.; Glowacki, I.; Kurach, E.; Rybakiewicz, R.; Kotwica, K.; Zagorska, M.; Pron, A.; Tassini, P.; Maglione, M. G.; De Girolamo Del Mauro, A.; Fasolino, T.; et al. (Opt. Mater., 2014)

(untitled) - Klyuchnikova, O. A.; Yudashkin, A. V. (Izv. Vyssh. Uchebn. Zaved., Khim. Khim. Tekhnol., 2005)

(untitled) - Kostyuchenko, A. S.; Averkov, A. M.; Fisyuk, A. S. (Org. Lett., 2014)

(untitled) - Gally, C. (Synthesis, 1979)

(untitled) - Jiang, Y.; Chen, X.; Zheng, Y.; Xue, Z.; Shu, C.; Yuan, W.; Zhang, X. (Angew. Chem., Int. Ed., 2011)

Comprehensive Heterocyclic Chemistry III - Suwiński, J.; Szczepankiewicz, W. (1,3,4-Oxadiazoles, 2008)

Comprehensive Heterocyclic Chemistry III - Koutentis, P. A.; Constantinides, C. P. (1,3,4-Thiadiazoles, 2008)

Comprehensive Heterocyclic Chemistry III - Curtis, A. D. M.; Jennings, N. (1,2,4-Triazoles, 2008)

(untitled) - Wang, Y.-G.; Huang, X.; Wu, Y.-Z. (Tetrahedron, 2007)

(untitled) - Chiriac, C. I. (Rev. Roum. Chim., 1982)

(untitled) - Kakefuda, A.; Suzuki, T.; Tobe, T.; Tahara, A.; Sakamoto, S.; Tsukamoto, S-i. (Bioorg. Med. Chem., 2002)

(untitled) - Korotkikh, N. I.; Kiselev, A. V.; Knishevitsky, A. V.; Raenko, G. F.; Pekhtereva, T. M.; Shvaika, O. P. (Chem. Heterocycl. Compd., 2005)

(untitled) - Liu, G.; Wu, X.; Shi, X. (J. Heterocycl. Chem., 2013)

Physical Methodes in Heterocyclic Chemistry - Armarego, W. L. F. (Ultraviolet Spectra of Heterocycles, 1971)

Einführung in die Photochemie - Becker, H. G. O.; Böttcher, H.; Dietz, F.; El‘cov, A. V.; Rehorek, D.; Roewer, G.; Schiller, K.; Studzinskij, O. P.; Timpe, H.-J. (Thieme, 1983)